An Investigation into the Effects of Ubiquinone on Inflammation, Diabetic Myopathy and Endotheliopathy, and CBC Parameters in Diabetic Rats - Jameel Jbrael, Yousif; Badraldin Kareem Hamad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Oxidative stress and inflammation are connected to the development of metabolic disorders, such as diabetes. Diabetic-related oxidative stress is caused by the overproduction of oxidative-free radicals, which have been implicated in the mechanism of inflammation and damage to tissues. Our study aimed to investigate the effects of ubiquinone treatment on serum indicators of oxidative stress (malondialdehyde (MDA)), inflammation (interleukin 6 (IL-6)), vascular homeostasis (nitric oxide (NO)), and myopathy (myoglobin (MB)) in addition to measuring blood components parameters in streptozotocin-induced diabetic rats. Rats were separated into three groups; negative control group (N), diabetic control group (D), and ubiquinone-treated diabetic group (T). After 21 days, the blood and serum samples were taken to evaluate fasting blood glucose (FBG), MDA, IL-6, NO, MB, and hematological parameters. In hyperglycemic rats, the levels of FBG and serum levels of IL-6, MDA, and MB significantly increased, while NO levels decreased. Hyperglycemic condition significantly lowered the count of WBC (P = 0.0098) but insignificantly decreased values of platelets and RBC. Ubiquinone treatment significantly reduced blood glucose, IL-6, MDA, and MB levels in diabetic rats and raised NO levels. The effects of ubiquinone on WBC (P = 0.648), RBC (P = 0.001), and (P = 0.398) were insignificant, and only minor variations in WBC and platelet levels were observed. Our data support that ubiquinone supplementation could reduce proinflammation, oxidative stress, and myopathy markers and elevate NO levels in diabetic rats. The current study indicates ubiquinone may positively impact diabetic complications; however, additional research is required to determine its therapeutic benefit when added to standard diabetes treatment.